Sheehan's syndrome. (18th December 2012) - Kilicli, Fatih; Dokmetas, Hatice Sebila; Acibucu, Fettah
Abstract: Sheehan's syndrome (SS) is characterized by various degrees of hypopituitarism, and develops as a result of ischemic pituitary necrosis due to severe postpartum hemorrhage. Increased pituitary volume, small sella size, disseminated intravascular coagulation and autoimmunity are the proposed factors in the pathogenesis of SS. Hormonal insufficiencies, ranging from single pituitary hormone insufficiency to total hypopituitarism, are observed in patients. The ﬁrst most important issue in the diagnosis is being aware of the syndrome. Lack of lactation and failure of menstrual resumption after delivery that complicated with severe hemorrhage are the most important clues in diagnosing SS. The most frequent endocrine disorders are the deficiencies of growth hormone and prolactin. In patients with typical obstetric history, prolactin response to TRH seems to be the most sensitive screening test in diagnosing SS. Other than typical pituitary deficiency, symptoms such as anemia, pancytopenia, osteoporosis, impairment in cognitive functions and impairment in the quality of life are also present in these patients. Treatment of SS is based on the appropriate replacement of deficient hormones. Growth hormone replacement has been found to have positive effects; however, risk to benefit ratio, side effects and cost of the treatment should be taken into account.